A circular economy in electric vehicle batteries : a european perspective - Walz, Phillip Niklas (2021)
Electrification of the automotive industry is an imperative for achieving the sustainability goals of various multilateral agreements. Battery electric vehicles (BEVs) have advantages over internal combustion engines, but lithium-ion batteries, the major component of the BEV powertrain, have significant environmental footprints. Circular economy concepts can mitigate these negative impacts and externalities via closed loop resource systems and second life applications for lifetime extension. The Circular Economy is still in its infancy, but regulation and moves towards decarbonization are strong drivers. This thesis discusses how second life applications associated with the Circular Economy are hindered by technical and economic factors. They compete with closed loop ambitions of recycling activities and market opportunities in the energy storage area are immature. In particular, less than 20-30% of batteries will have a second life. According to experts, battery recycling may become more tenable as increasing numbers of spent batteries enter the market. Scenario planning has shown that the prognosis for Circular Economy in electric vehicle batteries 5 to 10 years from now is optimistic. This scenario is characterized by the highest adoption of Circular Economy levels possible at this time. A consumer survey indicated that consumers fully support the transition to a Circular Economy and are not an impediment to this transition.